THE MODERN EDUCATIONAL SITUATION: DESCRIPTIVE APPROACHES AND DISCURSIVE RESPONSIBILITY - Alexander A. Polonnikov (Высшее образование в России)
The article deals with the methodology of analysis of the current higher education state. The two main descriptive critical strategies are highlighted: transcendent and immanent ones. The immanent strategy is implemented in two forms, those of "realistic" and "linguistically mediated" criticism, each of them being related to a specific definition of the educational situation. The definition of the educational situation is a base condition for the organization of the pedagogical order, its eventfulness and practical repercussions. The author substantiates the necessity of criticizing the language of the higher school pedagogy.